Dynamics of transcriptome and chromatin accessibility revealed sequential regulation of potential transcription factors during the brown adipose tissue whitening in rabbits - Du, Kun; Chen, Guan-He; Bai, Xue; Chen, Li; Hu, Shen-Qiang; Li, Yan-Hong; Wang, Guo-Ze; He, Jing-Wei; Lai, Song-Jia (Frontiers in Cell and Developmental Biology, 2022)
Brown adipose tissue (BAT) represents a valuable target for treating obesity in humans. BAT losses of thermogenic capacity and gains a “white adipose tissue-like (WAT-like)” phenotype (BAT whitening) under thermoneutral environments, which could lead to potential low therapy responsiveness in BAT-based obesity treatments. However, the epigenetic mechanisms of BAT whitening remain largely unknown. In this study, BATs were collected from rabbits at day0 (D0), D15, D85, and 2 years (Y2). RNA-sequencing (RNA-seq) and the assay for transposase-accessible chromatin with high-throughput sequencing (ATAC-seq) were performed to investigate transcriptome and chromatin accessibility of BATs at the four whitening stages, respectively. Our data showed that many genes and chromatin accessible regions (refer to as “peaks”) were identified as significantly changed during BAT whitening in rabbits. The BAT-selective genes downregulated while WAT-selective genes upregulated from D0 to Y2, and the de novo lipogenesis-related genes reached the highest expression levels at D85. Both the highly expressed genes and accessible regions in Y2 were significantly enriched in immune response-related signal pathways. Analysis of different relationships between peaks and their nearby genes found an increased proportion of the synchronous changes between chromatin accessibility and gene expression during BAT whitening. The synergistic changes between the chromatin accessibility of promoter and the gene expression were found in the key adipose genes. The upregulated genes which contained increased peaks were significantly enriched in the PI3K-Akt signaling pathway, steroid biosynthesis, TGF-beta signaling pathway, osteoclast differentiation, and dilated cardiomyopathy. Moreover, the footprinting analysis suggested that sequential regulation of potential transcription factors (TFs) mediated the loss of thermogenic phenotype and the gain of a WAT-like phenotype of BAT. In conclusion, our study provided the transcriptional and epigenetic frameworks for understanding BAT whitening in rabbits for the first time and might facilitate potential insights into BAT-based obesity treatments.